Validity of research-based e-module on conservation theme to environmental literacy attitude of junior high school students - Annisa Qurotul Aini; Suroso Mukti Leksono; Septi Kurniasih (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2024)
Ujung Kulon National Park is a national park with a lot of biodiversity that is almost extinct, but it has still not been realized by many students. Students' understanding and concern for the flora and fauna found in the TNUK area can be trained through learning based on environmental literacy. This study aims to determine the validity level of research-based e-modules on conservation themes to train environmental literacy attitudes of junior high school students. The research method used is research and development Research and Development R & D) concerning Thiagarajan, then adapted to the capabilities and needs of researchers, it is limited to 3 stages: define, design, and develop. The instrument used is a validation instrument sheet, which three validators will carry out, each on material expert validation, media expert validation, and teaching materials expert. The validation results obtained on the material expert get a percentage value of 82.88% with the category